Nontraditional community-college students with children: what it means to persist to degree - Peterson, Sally, author; Kuk, Linda, advisor; Mallette, Dawn, advisor; Scott, Malcolm, committee member; Quick, Don, committee member (Colorado State University. Libraries, 2014)
Fifteen nontraditional community-college student-parents from three Mountain West colleges participated in this phenomenological study, which describes the participants' experiences after they had delayed college attendance and then became full-time students while parenting, working part-time, and managing academic responsibilities. The purposeful sample of student-parents represented mixed demographics: three men and 12 women, ages 21 to 43; marital status of nine single parents and six married parents; diverse backgrounds; three college drop-outs; one participant with a bachelor of science degree; four military veterans; two participants who had completed drug/alcohol rehabilitation; and all participants with a child under kindergarten age. The methodology included a 90-minute interview with open-ended questions, interpretive phenomenological analysis, and the delineation of five themes that emerged from the findings of the student-parents' shared experiences. The themes revealed that student-parents attended college to increase their skills and knowledge with the goal of bettering their lives and the lives of their families through a meaningful career. The student-parents had varied interests, abilities, and career goals, and they faced numerous challenges while they attended college. Student-parents appeared to focus on completion of their degree by prioritizing responsibilities and making decisions that would allow them to be financially, academically, and parentally successful despite challenges. Their specific stress factors, coping strategies, and time prioritization were similar, yet some were unique to the individual. Balancing physiological, mental, and emotional needs was important to the participants while they focused on passing the tests necessary to accomplish their goals. Parenting strategies included shared study with the child when the mode was fun or engaging. Focused study required an environment free of distraction. Parents agreed that a positive mindset was a motivation for persistence. These student-parents' experiences, strategies, and resolve to finish offer guidance to community-college faculty, administration, counselors, advisors, support services, and other community-college student-parents in the associate-degree completion process.
Keywords: children; community college; degree completion; nontraditional; persist; student-parents